COTTON PNEUMOTRANSPORT PIPELINE CONTROL THROUGH MECHATRONIC (SCADA) SYSTEM - KHOLBAEV, DONIYOR (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
In the article, the results of the research of the change of air speed and aerodynamic force in the cross-section of the pipe during transportation of cotton, seed, lint, fiber waste from the separator cyclone, cyclonic fluff in pneumatic transport are reflected.